TIM‐4 increases the proportion of CD4+CD25+FOXP3+ regulatory T cells in the pancreatic ductal adenocarcinoma microenvironment by inhibiting IL‐6 secretion - Ziyao Wang; Zerong Xie; Yu Mou; Ruiman Geng; Chen Chen; Nengwen Ke (Cancer Medicine)
Abstract Background Currently, creating more effector T cells and augmenting their functions is a focal point in pancreatic ductal adenocarcinoma (PDAC) treatment research. T cell immunoglobulin domain and mucin domain molecule 4 (TIM‐4), known for promoting cancer progression in various malignancies, is implicated in the suppressive immune microenvironment of tumors. Analyzing of the role of TIM‐4 in the immune regulation of PDAC can offer novel insights for immune therapy. Methods We analyzed the TIM‐4 expression in tumor specimens from PDAC patients. Meanwhile, multiple fluorescent immunohistochemical staining was used to study the distribution characteristics of TIM‐4, and through tissue microarrays, we explored its correlation with patient prognosis. The influence of TIM‐4 overexpression on cell function was analyzed using RNA‐seq. Flow cytometry and ELISA were used for verification. Finally, the relationship between TIM‐4 and T lymphocytes was analyzed by tissue microarray, and the impacts of TIM‐4 on T cell subsets were observed by cell coculture technology and a mouse pancreatic cancer in situ model. Results In PDAC, TIM‐4 is mainly expressed in tumor cells and negatively correlated with patient prognosis. TIM‐4 influences the differentiation of Treg by inhibiting IL‐6 secretion in pancreatic cancer cells and facilitates the proliferation of pancreatic cancer in mice. Additionally, the mechanism may be through the CD8+ effector T cells (CD8+Tc). Conclusion TIM‐4 has the potential to be an immunotherapeutic target or to improve the efficacy of chemotherapy for PDAC.